Utility of dermoscopy for evaluating the therapeutic efficacy of tacrolimus ointment plus 308-nm excimer laser combination therapy in localized vitiligo patients - Wang, Lu-Mei (Exp Ther Med, 2018)
The aim of the present study was to assess the function of dermoscopy in evaluating the therapeutic efficacy of tacrolimus ointment plus 308-nm excimer laser combination therapy in patients with localized vitiligo. A total of 147 patients with localized vitiligo (progressive disease, n=92; stable period, n=55) were enrolled and received combination therapy for 12 weeks. The condition of the skin lesions was monitored by dermoscopy and visual observation. At the initial visit, skin lesions were observed in 61 progressive and 19 stable patients. Residual perifollicular pigmentation was more abundant in progressive-stage patients than in stable-stage patients, whereas the presence of perilesional hyperpigmentation was obviously lower in patients with progressive vitiligo. After 12 weeks of combination therapy, marked differences in residual perifollicular pigmentation were identified between the progressive- and stable-stage patients. Dermoscopy and visual observation indicated that the 12-week treatment efficacy in patients with progressive disease was significantly higher than in those with stable disease and that assessment by dermoscopy was superior to visual observation at 8 or 12 weeks of treatment. Binary logistic regression analysis revealed that the disease stage, vitiliginous areas and disease course were risk factors associated with the treatment efficacy of the combination therapy. In conclusion, dermoscopy may be used as an effective means of vitiligo therapy assessment to provide an accurate and scientific evaluation of treatment efficacy for localized vitiligo patients.